Ali Pierce: capstone - Pierce, Ali, artist (Colorado State University. Libraries, 2024)
The artist's statement: The current visual landscape is incredibly saturate. It seems like everywhere you look, there's optical stimuli fighting for acknowledgement. It's exhausting. In my design practice, I aspire to create imagery that not only grabs viewers' attention but keeps it. I catch eyes by utilizing vibrantly demanding colors and intentional secondary elements that provoke further consideration from the spectator. This can be a play on words, unique illustrations based on backstories, or analog elements like collage that are a bit out of the ordinary. When creating a poster zine detailing cardiovascular disease prevention research, I titled the primary poster "vastacular," combining the words vascular and spectacular to reiterate the positive impact of CVD deterrence. As I designed a T-shirt for United Way of Larimer County, I incorporated landmarks from their regional areas of focus into the illustration, including Horsetooth for Fort Collins, Devils Backbone for Loveland, and Dream Lake in Rocky Mountain National Park for Estes. These components invite audiences to take a closer look at my designs and reflect on the associated stories they tell. I am particularly passionate about messaging that advocated for human rights and promotes positive mental health, creating visuals that can have a deeper impact.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design